2018
DOI: 10.1016/j.cpc.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

SQDFT: Spectral Quadrature method for large-scale parallel O(N) Kohn–Sham calculations at high temperature

Abstract: We present SQDFT: a large-scale parallel implementation of the Spectral Quadrature (SQ) method for O(N) Kohn-Sham Density Functional Theory (DFT) calculations at high temperature. Specifically, we develop an efficient and scalable finite-difference implementation of the infinite-cell Clenshaw-Curtis SQ approach, in which results for the infinite crystal are obtained by expressing quantities of interest as bilinear forms or sums of bilinear forms, that are then approximated by spatially localized Clenshaw-Curti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 75 publications
0
50
0
Order By: Relevance
“…KSSOLV [10] is one such Matlab code for the planewave method, traditionally the discretization of choice in Kohn-Sham DFT [11,12,13,14,15,16]. However, to the best of our knowledge, no such counterpart exists for real-space methods, which have gained significant attention recently [17,18,19,20,21,22,23,24], in part due to their high scalability for large-scale parallel computing [25,23,24], flexibility in the choice of boundary conditions [26,27,28], and amenability to the development of linear scaling methods [29,8]. Motivated by this, in this work we develop M-SPARC: Matlab-Simulation Package for Ab-initio Realspace Calculations.…”
Section: Motivation and Significancementioning
confidence: 99%
“…KSSOLV [10] is one such Matlab code for the planewave method, traditionally the discretization of choice in Kohn-Sham DFT [11,12,13,14,15,16]. However, to the best of our knowledge, no such counterpart exists for real-space methods, which have gained significant attention recently [17,18,19,20,21,22,23,24], in part due to their high scalability for large-scale parallel computing [25,23,24], flexibility in the choice of boundary conditions [26,27,28], and amenability to the development of linear scaling methods [29,8]. Motivated by this, in this work we develop M-SPARC: Matlab-Simulation Package for Ab-initio Realspace Calculations.…”
Section: Motivation and Significancementioning
confidence: 99%
“…It also showed that purification methods using Chebyshev polynomials are equivalent to the use of Clenshaw-Curtis quadratures. This understanding led to a series of efficient algorithms using spectral quadratures [45,58] and applications to first-principles molecular dynamics [58,67,50].…”
Section: Introductionmentioning
confidence: 99%
“…The first goal of this work is to retain the efficiency of LSSGQ, but also extend it to nonlocal pseudopotentials. This requires a methodological advance that combines ideas of Ponga et al [42] and Suryanarayana et al [58]. As noted above, LSSGQ efficiently computes the energy and electron density using the Lanczos iteration since these only depend on the diagonal component of the density matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these preconditioners have a diagonal representation in Fourier space, they are easy and efficient to apply within the planewave method, but are unsuitable for real-space methods, where they take a global form. Given that realspace codes are now able to outperform their planewave counterparts by being able to leverage large-scale computational resources [26,27], while being amenable to the development of linearscaling methods [28,29] and offering the flexibility in choice of boundary conditions [30,31,32], efficient real-space analogues for such preconditioners are highly desired.…”
Section: Introductionmentioning
confidence: 99%